TC003132 is essential for the follicle stem cell lineage in telotrophic Tribolium oogenesis - Matthias Teuscher; Nadi Ströhlein; Markus Birkenbach; Dorothea Schultheis; Michael Schoppmeier (Frontiers in Zoology, 2017)
Abstract Background Stem cells are undifferentiated cells with a potential for self-renewal, which are essential to support normal development and homeostasis. To gain insight into the molecular mechanisms underlying adult stem cell biology and organ evolution, we use the telotrophic ovary of the beetle Tribolium. To this end, we participated in a large-scale RNAi screen in the red flour beetle Tribolium, which identified functions in embryonic and postembryonic development for more than half of the Tribolium genes. Results We identified TC003132 as candidate gene for the follicle stem cell linage in telotrophic Tribolium oogenesis. TC003132 belongs to the Casein Kinase 2 substrate family (CK2S), which in humans is associated with the proliferative activity of different cancers. Upon TC003132 RNAi, central pre-follicular cells are lost, which results in termination of oogenesis. Given that also Notch-signalling is required to promote the mitotic activity of central pre-follicular cells, we performed epistasis experiments with Notch and cut. In addition, we identified a putative follicle stem cell population by monitoring the mitotic pattern of wild type and TC003132 depleted follicle cells by EdU incorporations. In TC003132 RNAi these putative FSCs cease the expression of differentiation makers and are eventually lost. Conclusions TC003132 depleted pre-follicular cells neither react to mitosis or endocycle stimulating signals, suggesting that TC003132 provides competence for differentiation cues. This may resemble the situation in C. elegans were CK2 is required to maintain the balance between proliferation and differentiation in the germ line. Since the earliest effect of TC003132 RNAi is characterized by the loss of putative FSCs, we posit that TC003132 crucially contributes to the proliferation or maintenance of follicle stem cells in the telotrophic Tribolium ovary.